2018
DOI: 10.1016/j.foodhyd.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oat components on lipid digestion using an in vitro model: Impact of viscosity and depletion flocculation mechanism

Abstract: Depletion flocculation is a well-known instability mechanism that can occur in oil-in-water emulsions when the concentration of non-adsorbed polysaccharide exceeds a certain level. This critical flocculation concentration depends on the molecular characteristics of the polysaccharide molecules, such as their molecular weight and hydrodynamic radius. In this study, a range of analytical methods (dynamic shear rheology, optical microscopy, and static light-scattering) were used to investigate the interaction bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…On the contrary, in the present study the oil bodies did not appear to coalesce in the oat endosperm ( Figures 2A1 and A2), but they tended to flocculate once extracted from the oat matrix ( Figures 2B1 and B2). This phenomenon was recorded in our recent work where depletion flocculation of sunflower oil droplets was induced by the β-glucan released from the oat matrix following incubation of oat flakes and flour (Grundy, McClements, Ballance, & Wilde, 2018). However, no β-glucan was detected in the oil body preparation when stained with a dye specific to the polysaccharide, i.e., calcofluor white (data not shown).…”
Section: Characterisation Of the Oat And Sunflower Materialssupporting
confidence: 67%
See 2 more Smart Citations
“…On the contrary, in the present study the oil bodies did not appear to coalesce in the oat endosperm ( Figures 2A1 and A2), but they tended to flocculate once extracted from the oat matrix ( Figures 2B1 and B2). This phenomenon was recorded in our recent work where depletion flocculation of sunflower oil droplets was induced by the β-glucan released from the oat matrix following incubation of oat flakes and flour (Grundy, McClements, Ballance, & Wilde, 2018). However, no β-glucan was detected in the oil body preparation when stained with a dye specific to the polysaccharide, i.e., calcofluor white (data not shown).…”
Section: Characterisation Of the Oat And Sunflower Materialssupporting
confidence: 67%
“…Almond oil bodies have been shown to form similar structures during gastric digestion than to the ones observed in Figure 3C, some of the almond proteins being resistant to pepsin activity (Gallier & Singh, 2012). Hence, the network formed by a combination of compounds (possibly proteins, phytosterols, galactolipids, saponins, and phospholipids) around, or at the vicinity, of the droplets is likely to have hindered the access of the lipase to its substrate (Chu et al, 2009;Grundy, McClements, Ballance, & Wilde, 2018). Flocculated oil bodies could be clearly seen in Figures 3C3 and C4 confirming that these newly formed structures were difficult to degrade.…”
Section: Lipolysis Kineticsmentioning
confidence: 94%
See 1 more Smart Citation
“…Also, it should be mentioned that carbohydrates provide the necessary energy for the body and influence the nutraceutical release by enhancing the viscosity of the food matrix. Certain authors showed that the use of diet fibers (chitosan, sodium alginate, and locust bean gum) influences the size and electrical properties of oil droplets, the viscosity of nanoemulsions, and the formation of FFAs by the nanoemulsion digestion (Grundy, McClements, Ballance, & Peter, 2018; Qin et al., 2017).…”
Section: External Factors Affecting the Nutraceutical Bioavailabilitymentioning
confidence: 99%
“…The magnitude of the osmotic attraction increases with increasing hydrocolloid concentration and eventually it can become large enough to overcome any repulsive forces and promote flocculation. Both theoretical and experimental studies have shown that there can be a substantial increase in emulsion viscosity due to depletion flocculation, as well as the generation of a yield stress (Berli, ; Berli et al, ; Grundy, McClements, Ballance, & Wilde, ; Preziosi et al, ). This phenomenon may therefore be utilized to create novel textural characteristics in food emulsions. Bridging flocculation : This kind of droplet aggregation occurs when a hydrocolloid links two or more oil droplets together (Dickinson, ).…”
Section: Impact Factors Of Emulsion Rheologymentioning
confidence: 99%